The CORE Learning Model (Connecting, Organizing, Reflecting, and Extending): How Does Its Implementation Affect Learning Outcomes at the C5 Level? - Nurfala, Audyla; Istihana, Istihana; Sunarto, Sunarto (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study examines the effectiveness of the CORE (Connecting, Organizing, Reflecting, and Extending) learning model in enhancing students' evaluative cognitive skills (C5) in Islamic Religious Education (IRE) at the junior high school level. The gap between the need for teaching that fosters higher-order thinking skills and the current teaching practices, which are still dominated by a lecture-based approach, provides the backdrop for this research. A quantitative approach with a Posttest-Only Control Group design was used, involving two classes selected through cluster random sampling. The analysis results show a significant difference in evaluative abilities between the experimental group and the control group, confirming that the CORE model has a positive impact on facilitating critical thinking and argument-based decision-making. These findings provide strong empirical support to reinforce the constructivist approach in IRE teaching and recommend expanding the application of the CORE model to more diverse contexts and cognitive domains in the future.